O FEMININO E O MASCULINO NA FORMAÇÃO DISCURSIVA DA GASTRONOMIA: EFEITOS DE MEMÓRIA E IDEOLOGIA - Godoy, Ana Carolina de (2017)
This thesis intends to analyses the discourse of the Gastronomy, that means as a social, anthropological and historical phenomenon, around subjects who works in this area, subscribing in gastronomy discursive formation and constituting by the same subject-position. Despite of this, in the discourse about these subjects that circulated on media, different sense effects are established by imaginary and by the symbolic. We think with the Discourse Analyses and we analyze our text by the memory and ideology. Our goal is to verify which memories and discourses support and make natural the imaginary about feminine-subject and masculine-subject in the cuisine, when they are on the leadership discursive position. Our research question is: “Which memories and discourses supporting the simulacrum by which the cuisine, and its works, are natural for the women, and the men, in the same place, breaks stability and installs an discursive event, or at least, enunciative?” Analyses allow us to affirm that discourses about feminine-subjects in Gastronomy show that when these subjects are on cuisine, they are on their natural place, making homogeneity, linear repetition and stabilization evidences in discourses. On the other hand, the masculine-subjects, in the same place and position, install the newness and break effects in discourses formulated and in circulation in the Gastronomy. The corpus of our research is built by discourses that circulated in specialized magazines that control the sense, which reproduces and transform the social formation, by the repetition or by rupture in reproduced discourses. In order to attending our goals, we use the theoretical field of Discourse Analyses, specifically, memories that return, resonate and produce sense effects that break, or not, the established linearity. In this research, we highlight the discursive memory making it different of interdiscourse and approaching this to the discursive formation of Gastronomy. In this discursive formation, feminine and masculine subjects occupy the same subject-position, but they install the contradiction, in view of the operation of more than one subjectposition. Homogeneity effects, in this discourses, result of ideology work and historicity that continues to determinate the women’s place and the men’s place, determining what each one can/must to do or not, according with the socio-historical of each discourse in relation to the subject.